Seguridad Basada en el Comportamiento: Hacia una cultura del trabajo seguro - Pariona-Palomino, Jordy (2021)
Occupational accidents have become one of the most important challenges for organizations to address. It is urgent to take measures to avoid continuing losses in terms of human and economic resources. During the last decades, Behavior-Based Safety (BBS) has been considered an effective methodology aimed at determining the antecedents that lead to risky behavior. It focuses on promoting a preventive safety culture avoiding accidents and occupational diseases in the workplace. The study is aimed at the systematic review of the available literature on the key aspects for the management and implementation of BBS, as well as the findings that have been found after its application. Keywords were used in database search engines and only the most relevant in English were considered. Five common elements were found for the BBS, in addition, 99% of the studies showed a substantial improvement thanks to this program. The BBS presents a general approach to address the issue of substandard behavior. The BBS also helps to strengthen planned activities in a safety management system by changing unsafe behaviors to safe ones.